Cover Image, Volume 88, Issue 6. (16th July 2018) - Indran, Inthrani R.; Huang, Zhongwei; Khin, Lay Wai; Chan, Jerry K.Y.; Viardot‐Foucault, Veronique; Yong, Eu Leong
Abstract : The cover image, by Inthrani R. Indran et al., is based on the Original Article Simplified 4‐item criteria for polycystic ovary syndrome: A bridge too far?, DOI:10.1111/cen.13755 .